La guerre franco-prussienne << traduite >> à la littérature: Les Soirées de Médan - Dobrescu, Andreea-Roxana (Études sur la Région Méditerranéenne, 2020)
War and literature are two words that are in a fruitful relationship, the first one being the raw mineral that the second one is striving to polish to obtain a stylistic and stylised product. This paper tries to reveal the reality of the Franco-German war and the profile of the two nations involved in the conflict. Our aim is to present the destructive effects of the war, using as instrument of analysis an important word of the collection: agony. Thereby, this paper is structured into three chapters, constructed according to the different meanings attributed to this key-word. The first chapter is conceived by considering the basic meaning of the word agony, i.e. intense physical sufferance before death, in order to reveal the violence of the war, the dehumanization, the physical violence, opposing the two peoples fighting in the war. This section will attempt to emphasize the existing rapport between the two countries during the armed conflict, but also its devastating effects, at an individual level. Consequently, the textual support will be offered by the male characters of Evenings at Médan. The second section is concentrated on the philosophical meaning of the word agony, understood as moral torment, anguish, unease. In accordance with this sense, our objective is to present the consequences of the war as regarding the female characters, abandoned, without protection, without help, being the victims of the soldiers’ abuse. The last chapter is constructed so as to develop the abstract meaning of agony which refers to the decline of a political regime, of an existent system, resuming precisely the situation of Evenings at Médan. The violent fight between the two nations affects irreversibly the situation of France, its general equilibrium and its image, ending with a shaming defeat.